2020
DOI: 10.3390/cells9030731
|View full text |Cite
|
Sign up to set email alerts
|

The Leader Position of Mesenchymal Cells Expressing N-Cadherin in the Collective Migration of Epithelial Cancer

Abstract: Understanding how heterogeneous cancer cell populations migrate collectively is of paramount importance to arrest metastasis. Here, we applied 3D culture-based approaches for in vitro modeling of the collective migration of squamous carcinoma cells and examine the impact of epithelial and mesenchymal cell interactions on this type of migration. We show that both mesenchymal N-cadherin-expressing cancer cells and cancer-associated fibroblasts cooperate in collective migration of epithelial cancer cells by leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
4
16
0
Order By: Relevance
“…As recently reported [ 26 ], SCC38 and SCC42B cells assembled as multicellular spheroids in collagen matrix migrate as a collective unit following an outwards and downwards direction as observed upon three-dimensional reconstructions of Z-stacked images taken after 24 h of culture ( Figure 1 A).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…As recently reported [ 26 ], SCC38 and SCC42B cells assembled as multicellular spheroids in collagen matrix migrate as a collective unit following an outwards and downwards direction as observed upon three-dimensional reconstructions of Z-stacked images taken after 24 h of culture ( Figure 1 A).…”
Section: Resultssupporting
confidence: 81%
“…The effect of FAK on collective cell invasion was not a cell-line-specific function. In addition to SCC42B cells, we also analyzed SCC38 cells which have greater invasive activity than SCC42B [ 26 ] and express higher levels of FAK and pFAK protein ( Figure S2 ). FRNK-induced inhibition of FAK activity in SCC38 cells (FR-SCC38) ( Figure S2 ) also impaired collective invasion (37-fold decrease in mean SCSA, p < 0.0001, Figure 1 F) compared with control cells (C-SCC38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Gopal et al identified oncofetal fibronectin (FN) as a major and obligate component of the matrix assembled by stromal fibroblasts from head and neck squamous cell carcinomas (HNSCC) [44]. Moreover, Saénz-de-Santa-María et al showed that the presence of "leader" mesenchymal cancer cells or "leader" fibroblasts was significantly associated with metastasis development, recurrent disease and low overall disease survival in head and neck squamous cell carcinomas [45]. On the other hand, whether cancer cells in lymph nodes can seed distant metastases has been a subject of considerable debate.…”
Section: Discussionmentioning
confidence: 99%